Black Butterflyz - Omni, Christal (My University, 2019)
Black Butterflyz’ Flyz with Ease: An Integrative Pilot Walk With Ease experience for Black women, fell under the Kansas Department of Health and Environment Division 3, Public Health, programming. Walk with Ease is an Arthritis Foundation evidence-based walking program created by the University of North Carolina Chapel Hill in 1999 and then revised in 2009. My project, Flyz with Ease, offered an 18 session, targeted group method delivery system designed to improve the health and wellbeing of Black women in Topeka, KS.
Keywords: public health; black women health